PERAN MEDIA MASSA DI KALIMANTAN BARAT DALAM MEMPENGARUHI OPINI PUBLIK - Hasymi Rinaldi; Mahendra Jaya; Debbie Yuari Siallagan (JURUSAN ADMINISTRASI BISNIS POLITEKNIK NEGERI PONTIANAK, 2021)
Many theories support the ability of the mass media in constructing public opinion. Moreover, those theories are also supported by many researches showing the strategic position of mass media in influencing public opinion. The problem is that mass media is no longer the main source of information for many people. The number of disinformation news spreads very quickly through social media networks. The rapid spread of hoax news indicates that many people believe the truth of fake news. According to the phenomenon, this research seeks to identify the ability of the mass media, in this case print media, in influencing public opinion. The approach used in this research is qualitative with phenomenological method. Based on the data obtained and processed, shows that the mass media able to influence public opinion, although the mass media can also be influenced by the virality of information.